Pemantauan Remediasi Tanah Hasil Pembakaran Dengan Mikroorganisme Dalam Lumpur Sawah - Maitsa Fikri Nabila; Yulia Inka Suryawan; Wendi Febriansyah; Galih Ramdani (Program Studi Teknik Sipil, Fakultas Teknik Universitas Teknologi Sumbawa, 2025)
Microorganisms are widely distributed in various environments such as water, soil, dust, food, and even on the surface of human tissues. They consist of several groups including bacteria, fungi, and protozoa, and exist in large and diverse populations. One of the essential roles of microorganisms in the environment is their function in bioremediation, which is the process of breaking down or degrading pollutants into less toxic or non-toxic compounds. Soil is particularly vulnerable to contamination, especially from combustion activities, which can significantly deteriorate environmental quality and public health. This study aims to evaluate the potential of microorganisms found in rice field sludge as bioremediation agents for soil polluted by organic and inorganic substances resulting from burning. Rice field sludge contains a variety of microorganisms that produce specific enzymes capable of degrading complex compounds. By harnessing the natural bioremediation capabilities of these microorganisms, it is hoped that an effective and environmentally friendly solution to soil pollution can be achieved.